Assistance in the Issuance of Business Identification Number on Micro-Enterprises - Alfalisyado (Journal of Society, Community and Business Development, 2024)
This program aims to educate micro-entrepreneurs about the importance of having a Business Identification Number (NIB) and to disseminate information on the benefits associated with obtaining an NIB. Additionally, the program seeks to assist micro-entrepreneurs in acquiring their own NIBs. The activities conducted include observation, education, and mentoring for micro-entrepreneurs in the Karanglewas District. A total of twenty micro-entrepreneurs participated in the mentoring program until its completion. As a result of this program, there has been a significant increase in understanding and awareness among micro-entrepreneurs regarding the importance of having an NIB. Equally important, the participants successfully obtained their NIBs after the mentoring sessions.